1998
DOI: 10.1007/bf03164835
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of reduced cerebral metabolism in multiple sclerosis: A combined PET and MRI study

Abstract: Magnetic resonance imaging (MRI) in patients with multiple sclerosis (MS) has provided major insights into the disease's natural history, and many studies have focussed on possible correlations between MRI findings and the clinical manifestations of MS. In contrast, there are few reports on possible relationships between functional imaging data and cognitive function. The present study assessed the relationship between clinical presentation and combined anatomical and functional imaging data in MS. Twenty pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 23 publications
4
74
0
1
Order By: Relevance
“…29 Other possible underlying mechanisms were later suggested. Recent studies using MRI or metabolic PET studies 30,31 have highlighted a reduction of arterial inflow within the damaged white matter, particularly the periventricular normal-appearing white matter, 32,33 extending to the cerebral cortex and deep gray matter. Cerebral hypoperfusion in MS patients was mainly assumed to be secondary to reduced metabolic demand due to axonal degeneration.…”
Section: Venous Flowsmentioning
confidence: 99%
“…29 Other possible underlying mechanisms were later suggested. Recent studies using MRI or metabolic PET studies 30,31 have highlighted a reduction of arterial inflow within the damaged white matter, particularly the periventricular normal-appearing white matter, 32,33 extending to the cerebral cortex and deep gray matter. Cerebral hypoperfusion in MS patients was mainly assumed to be secondary to reduced metabolic demand due to axonal degeneration.…”
Section: Venous Flowsmentioning
confidence: 99%
“…Our results also raise the question of whether this imaging modality can be of value in monitoring the presence of inflammatory infiltrates in the human autoimmune demyelinating disorder MS. Several [ 18 F]FDG PET imaging studies on MS have been published during the last 15 years (39)(40)(41)(42)(43)(44)(45). Interestingly, however, the goal of these studies was not to detect and monitor inflammation but rather to determine whether the regional cerebral metabolic rate of glucose (rCMRGlc) estimated by using [ 18 F]FDG PET can be used as an indirect measurement of cortical impairment in MS.…”
Section: Potential Use Of [ 18 F]fdg Pet/ct In Msmentioning
confidence: 99%
“…One study by Sun et al (1998), using positron emission tomography (PET), which requires specific tracer such as 15 O, has demonstrated that there is cerebral hypometabolism in both gray matter (GM) and white matter (WM) of MS patients. The severity of cerebral hypometabolism was also related to the number of relapses in patients, suggesting that the measurement of oxygen metabolism has a potential role in monitoring disease activity and prognosis.…”
Section: Introductionmentioning
confidence: 99%